The church as paradise and the way therein : early Christian appropriation of Genesis 3:22-24 - Graham, Christopher A. (The Bible in Ancient Christianity, 2017)
In The Church as Paradise and the Way Therein: Early Christian Appropriation of Genesis 3:22-24 , Christopher A. Graham demonstrates that early Christian authors employed the words "paradise" and "way" as allusions to the expulsion narrative (Genesis 3:22-24) to signify that the benefits available in protological Paradise were once again accessible in and through Jesus and the Church. The centrality of the expulsion narrative in their literary milieus gave these authors confidence that readers would discern these allusions. After considering the reception of the expulsion in texts circulating within the early Christian milieu, Graham turns to the texts of Luke and Irenaeus of Lyons. Both authors drew from an interpretive tradition in which a return to Paradise was desirable. Both celebrated Jesus's reversal of Adam's expulsion and the constitution of Jesus's followers as the location and means by which humanity could continue to access divine truth and life. For both authors, the Church is Paradise and the way therein.